2022
DOI: 10.1101/2022.12.12.22283375
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genomic characterization of respiratory syncytial virus 2022-2023 outbreak in Washington State, USA

Abstract: Mitigation measures against the COVID-19 pandemic affected the RSV seasonality and led to an unexpectedly high number of RSV cases in Washington State since October 2022. Here we describe the RSV genomic characteristics and evolutionary relationship of 2022 outbreak compared to the previous RSV outbreaks in the region and globally.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 10 publications
3
10
0
Order By: Relevance
“…There was a notable expansion of an RSV‐B clade with distinct mutations compared to strains detected in the prepandemic seasons. While this lineage appears to be the only RSV‐B lineage circulating in the United States, where the late 2022 season has been predominated by RSV‐A, we detected additional RSV‐B sequences more similar to prepandemic lineages as well 6,7 . We tentatively refer to this as GB5.0.6a, as it satisfies the conventions outlined by Goya et al, 8 although this must be confirmed as more sequences become available from the 2022 to 2023 transmission season and future seasons.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…There was a notable expansion of an RSV‐B clade with distinct mutations compared to strains detected in the prepandemic seasons. While this lineage appears to be the only RSV‐B lineage circulating in the United States, where the late 2022 season has been predominated by RSV‐A, we detected additional RSV‐B sequences more similar to prepandemic lineages as well 6,7 . We tentatively refer to this as GB5.0.6a, as it satisfies the conventions outlined by Goya et al, 8 although this must be confirmed as more sequences become available from the 2022 to 2023 transmission season and future seasons.…”
Section: Discussionsupporting
confidence: 67%
“…Recent studies showed that this prolonged lack of virus exposure resulted in a decline of RSV‐specific immunity, 4,5 which may explain the earlier‐than‐usual start in 2021, but may not fully explain the drastic increase in cases in 2022. We were interested in testing whether the current surges were associated with genotypes potentially evading prior immunity, or novel genotypes with increased transmission or pathogenicity 6,7 . Therefore, we analyzed the molecular epidemiology of the recent RSV epidemics to better understand the phylodynamics of RSV and gain insight into the current surges.…”
Section: Introductionmentioning
confidence: 99%
“…There was a notable expansion of an RSV-B sublineage with distinct differences compared to strains detected in the pre-pandemic seasons. While this sublineage appears to be the only RSV-B lineage circulating in the US, where the late 2022 season has been predominated by RSV-A, we detected additional RSV-B sequences more similar to pre-pandemic sublineages as well [6]. RSV-A genotype GA2.3.5 was notably more diverse than RSV-B, and several well-supported sublineages were represented in 2022 as well as in the four prior seasons.…”
Section: Discussionmentioning
confidence: 87%
“…Recent studies showed that this prolonged lack of virus exposure resulted in a decline of RSV-specific immunity [4,5], which may explain the earlier-than-usual start in 2021, but may not fully explain the drastic increase in cases in 2022. An alternative or potentially additional hypothesis to explain the surge could be the emergence of novel genotypes with increased transmission or pathogenicity [6]. Therefore, we were interested in analysing the molecular epidemiology of the recent epidemics to better understand the phylodynamics of RSV.…”
mentioning
confidence: 99%
“…The 4 complete RSV-B genomes similarly yielded a tMRCA estimate of 2019 as the later bound ( Fig 1D , F; Fig S4B; Fig S5 ). Currently, the only other RSV genomes from the 2022 surge in the US are from Washington 2 (WA; N=39); the RSV-A genomes from WA belong to 6 lineages, of which 4 also contain MA genomes ( Fig 1C, E; Fig S4A , B ). The genetic divergence of the 2022 RSV-A and RSV-B genomes was consistent with our estimated clock rate from the larger phylogenetic tree (10.6 and 12.4 substitutions per year, respectively), in contrast with the accelerated evolution seen with the highly transmissible SARS-CoV-2 Alpha, Delta, and Omicron variants 35 .…”
Section: Mainmentioning
confidence: 99%